Urban and rural threat perceptions of China in Thailand: a longitudinal analysis from the Asian Barometer Survey - Meesuwan, Sanyarat; Setthasuravich, Prasongchai (Frontiers in Political Science, 2025)
This study examines how Thai citizens perceive China as a potential threat, with a focus on the differences between urban and rural populations. Using data from the Asian Barometer Survey’s third to sixth waves, spanning from 2010 to 2022, the analysis employs ordered probit regression to assess how residential location, democratic values, and trade protectionist attitudes influence perceptions of China’s influence in Thailand and across Asia. The study reveals a notable divide in how Thai citizens perceive China, with urban residents more inclined to view China as a threat compared to their rural counterparts. Urban skepticism reflects exposure to competitive markets, critical media, and global political discourse, which frame China’s regional behavior as a challenge to democratic norms and national autonomy. In contrast, rural populations tend to hold more neutral or positive views, likely influenced by the tangible material benefits derived from Chinese engagement, such as infrastructure investment and agricultural trade. The findings highlight the need for targeted policy responses in Thailand. Officials should implement targeted policy responses: increasing transparency in bilateral agreements, promoting civic oversight of foreign investment, and strengthening media literacy to address public distrust in urban areas. In rural areas, efforts should prioritize inclusive benefit-sharing and protecting local autonomy in development planning. For Chinese policymakers, the results underscore the limits of uniform public diplomacy, calling for adaptive strategies that respect Thailand’s internal diversity.